An investigation of the civil and defence aviation industry in 2025 using scenario planning - El Manialawi, Basma`; Younis, Ossama; Badr, Hind; Nilaus, Kasper (2006)
This management consulting project uses scenario planning to present the client, Rolls-Royce PLC, with possible pictures of the state of the aviation industry in 2025, covering both civil and defence aerospace.